EDITORIAL COMMENT - Vance, Stanley (Academy of Management Journal, 1967)
The article discusses the “Academy of Management Journal” as it moves from its third to fourth editor. The article states that the magazine has done well, citing that from 1958 to 1967, journal readership has increased to approximately 1,700. The author gives commendation to the first three editors and to host universities who have provided significant support to the journal. The author states that the journal has committed to continue encouraging investigation and scientific documentation.